Peluang Integrasi Eksisting Sistem Penjualan dengan Media Jejaring Sosial - Kridalukmana, Rinta (Jurnal Sistem Komputer, 2015)
Online social networks nowadays are not only used to connect individual users, but also become an opportunity that have been used by small business to offer products to other users by sharing information about their products and receiving order through social networks, even though most of the businesses already have website to work on it. The next challenge is to integrate the process above between business website and online social networks. This paper starts by providing overview about how businesses use online social network for commercial or marketing activities. By utilizing the Application Programming Interface (API) provided by online social networks, this study intends to explore the opportunities of integration between online social networks with the website that has been owned by the business